(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2024)
The political and administrative territorial divisions of a country or a regional state are the result of several elements. Population growth and the existence of economic activities that generate income to sustain the territory to be created are factors that justify the creation of landuse planning processes, as has been done with districts, parishes, municipalities, provinces or states. In addition, there are military, political, electoral, social and economic interests that allow control over some key areas and the increase in the number of public officials, among other aspects. The purpose of this work is to show the origins of the present Palavecino municipality in the state of Lara, Venezuela, and the different denominations it has received over time. Likewise, the different political territorial modifications that have taken place in this locality after the second half of the 20th century and in the first two decades of the 21st century are also discussed.